Hybrid Simulations of the Martian Magnetotail Twist - Jingyi Zhou; Kaijun Liu; Riku Jarvinen; Esa Kallio; Kun Cheng; Shuai Zhang; Qi Liu; Yuqi Liu; Yan Wang; Ruohan Wang; Xinye Wang; Xuanyu Shang; et al. (The Astrophysical Journal)
Three-dimensional global hybrid simulations are performed to explore how the interplanetary magnetic field (IMF), the Martian crustal fields, and planetary pickup ions affect the twisting of the Martian magnetotail. The results agree with previous studies that the crustal magnetic fields cause the Martian magnetotail to twist counterclockwise or clockwise depending on the sign of the IMF Y -component in the Mars solar orbital coordinates. However, the twist is more pronounced when the crustal fields are on the nightside, contradicting the early explanation that the crustal fields affect the twist through dayside magnetic reconnection between the crustal fields and the draped IMF. Additionally, planetary pickup ions also contribute to the twist because their mass loading slows down the plasma flow and leads to the bending of the magnetic field lines in the magnetotail. It is demonstrated that the twist inside Mars’ shadow in the near magnetotail region (at X = −1.5 R _M , where R _M is Mars’ radius) is mainly attributable to the crustal fields, while the influence of planetary pickup ions starts to dominate outside Mars’ shadow and in regions further away from Mars.